Toward a more perfect university - Cole, Jonathan R. (New York : PublicAffairs, 2016)
"A renowned academic leader identifies the ways America's great universities should evolve in the decades ahead to maintain their global preeminence and enhance their intellectual stature and social mission as higher education confronts the twenty-first-century developments in technology, humanities, culture, and economics."--Dust jacket.
"Jonathan R. Cole, former provost and current University Professor at Columbia University, addresses some of the biggest challenges facing the modern American university: developing effective admission policies; creating the most meaningful examinations; dealing with rising costs; making undergraduate education central to the university's mission; exploring the role of the humanities; facilitating new discoveries and innovation; determining the place for professional schools; developing the research campuses of the future; assessing the role of sports; designing leadership and governance; and combating intellectual and legal threats to academic freedom."--Publisher description.
Getting In -- Thoughts on Undergraduate Education and Its Future -- A House Built on a Firm Foundation -- The Contours of the University -- The Affordability and Value of Higher Education: Fact and Fiction -- An Accessible, High-Quality Education for All -- Creating New Academic Leagues and Knowledge Communities -- Reimagining the University Campus -- The Central Dogma of a Great University -- Reconstructing the University-Government Compact -- Structural Change.
Includes bibliographical references (pages [331]-389) and index.
MNS
Keywords: Universities and colleges -- United States; Universities and colleges -- United States -- Administration; Education, Higher -- United States; Education, Higher -- Curricula -- United States